Internal Auditor Competency Gap: Perception Of Students, Academics And Practitioners - Dyah Setyaningrum; Aria Farah Mita; Dini Rosdini (Universitas Muhammadiyah Malang, 2022)
The purpose of this study is to investigate internal auditor competency gap by comparing the perceptions between students, academics, and practitioner. Questionnaires were sent to 1009 respondents who meet the criteria using google form. The questionnaire was divided into two parts. The first part, we ask respondents’ perception related with hard skill needed by internal auditor, the second part discussed soft skill required to prepare agile and adaptive internal auditor. This study found two main gaps between three groups of respondents. First, there are competency gap related to technology and emerging risk. Internal auditor must update with agile audit methodologies and data analytics. The universities must enrich the internal audit course with current audit method and data analytic skills. Second, all respondents put emphasis on soft skill more than hard skill, therefore important soft skill for auditor should embedded in curricula. Academics and practitioners agree that hard skill competencies specially related with performance standards as mentioned on international standards is important knowledge that should possessed by internal auditor to performed internal audit role comprehensively.